Большие интегральные схемы запоминающих устройств - Гордонов А. Ю. Александр Юрьевич; Бекин Н. В. Николай Викторович; Цыркин В. В. Виктор Васильевич; Шеремет К. П.; Лаптева С. Б.; Дьяков Ю. Н. (Справочник)
Авторы указаны на обороте титульного листа